Fresh Semen Characteristics, Biochemical and Mineral Composition of Seminal Plasma from Different Age Groups of Balinese Cattle - Witri, Brilla Widya; Arifiantini, Iis; Prasetyaningtyas, Wahono Esthi; Karja, Ni Wayan Kurniani (Jurnal Medik Veteriner, 2025)
Age is among the factors affecting reproductive organs, particularly semen characteristics. Semen characteristics are also influenced by composition of seminal plasma that is ejaculated with the sperm. Therefore, this study aimed to investigate characteristics of fresh semen and seminal plasma composition from Balinese cattle aged 3, 8, and 13 years. Semen characteristics observed were concentration, progressive motility, viability, plasma membrane integrity, acrosome integrity, and sperm abnormalities. Biochemical composition of seminal plasma analyzed was fructose, malondialdehyde (MDA), total antioxidant capacity (TAC), glutamic oxaloacetic transaminase (GOT), glutamic pyruvic transaminase (GPT), total protein (TP), albumin, cholesterol, and triglycerides. Mineral compositions observed were Na, K, Ca, Mg, Zn, Cu, Fe, and Se. The results showed that there were no significant differences (p > 0.05) in semen characteristics across age groups, meaning that semen of Balinese cattle can still be processed into frozen semen even at an older age, provided it meets the SNI 4869-1:2024 standards. Furthermore, the concentrations of each seminal plasma biochemical component were as follows: fructose (377.5–615.4 mg/dL), MDA (9.7–10.36 nmol/mL), TAC (66.22–67.22%), GOT (203–265 U/L), GPT (19–35 U/L), TP (4.3–5.5 g/dL), albumin (1.7–1.9 g/dL), cholesterol (11–35 mg/dL), and triglycerides (822–1.078 mg/dL). Surprisingly, the concentration of triglycerides in semen plasma in this study was very high compared to those reported in previous studies on several cattle breeds. Seminal plasma mineral concentrations included Na (1.500–1.900 mg/kg), K (600–700 mg/kg), Ca (600–800 mg/kg), Mg (38.85–45.16 mg/kg), Zn (5.33–9.64 mg/kg), Cu (0.06–0.12 mg/kg), Fe (11.85–15.88 mg/kg), and Se (0.92–1.48 mg/kg). These findings indicate that age did not affect semen characteristics, biochemical, and mineral composition of seminal plasma in Balinese cattle.